Do Transfer Taxes Reduce Intergenerational Transfers?. Issue 1 (1st February 2014) - Jappelli, Tullio; Padula, Mario; Pica, Giovanni
Abstract: We estimate the effect of taxes on intergenerational transfers by exploiting a sequence of Italian reforms culminating with the abolishment of transfer taxes. We use the Surveys of Household Income and Wealth from 1993 to 2006, which have data on real estate transfers, and information on potential donors and recipients. Difference-in-differences estimates indicate that the abolition of transfer taxes increases the probability of high-wealth donors making a transfer by two percentage points and increases the area transferred by 9.3 square meters relative to poorer donors.